APLIKASI PEMESANAN BARANG DI NANCY TOYS MENGGUNAKAN APLIKASI WEB - Bagja, Rizky Ahmad Bagja (LPPM UNIKA Santo Thomas Medan, 2022)
Nancy toys toys that deal in retail sales for children/hobbyists have more than 90 regular customers outside the area, so there is a system of sales information needed to help the customer buy and receive the product information from the store. The web based retail information system aimed at helping the customer at Nancy toys can make online purchases without having to visit the store directly. In addition, this information system can be used as a platform for the promotion of child toy products/hobbies that can be easily transmitted directly. In this study using a qualitative type of descriptive research using the data-collection methods of observation, interviews and library studies. The purpose of this study is to design a system that can improve quality and bookmaking services as an effort to support the online business process. The design of the system USES PHP programming language, and mysql for its database and for testing it USES the black box methods. From this study results in a bookmaking system application, and it can be summarized to design and build a web-based bookmaking service system that can help Nancy toys to improve the quality of service and business from the effort.